Bad Santa [videorecording (DVD)] - Thornton, Billy Bob; Cox, Tony, 1958-; Graham, Lauren, 1967-; Ritter, John, 1948-2003; Mac, Bernie (Miramax, 2011)
Willie is a thief who teams up with his dwarf friend Marcus, for a very special Christmas scam. Willie gets a job as Santa Claus at a shopping mall, Marcus tags along as an elf, and they use their employee status to rob stores blind just before Christmas. But Willie is a bitter and foul-mouthed alcoholic who doesn't care much for kids. A mall's manager is certain something's wrong, so he asks the chief of security to check out Willie. Meanwhile, one of the kids Willie is forced to talk to becomes a regular customer.